Tendências e formas de enfrentamento da formação continuada, como profissionalização docente: um estudo em representações sociais - Bizerra, Carine Camara (2012)
This dissertation aimed at studying social representations about the teacher’s professionalization of teachers of Basic Education in the Lowlands. Being social representations forms of commonsense knowledge constructed in relations between individuals who mobilize practical worth studying this form of knowledge to understand the current trends of professionalization that still lack studies. By raising the studies that relate indexers "social representations", "teacher professionalization" and "teacher training" in the CAPES thesis database (1990 to 2000), among twenty-seven projects, only one comes to social representations. It covers studies to verify the pedagogical thinking in the last decade, a period of emergence of three new regulations about the Faculty of Education. It is against this backdrop, plus the experience of the author experienced the recognition of non-exercise of autonomy as a teacher, which traces the study of the subject since the origin of ideas / thoughts about the professionalization of teachers. Thus, we seek to understand the trajectory of teachers and their practices. So, the question is: what are the social representations of teacher professionalization and what practices are adopted in their actions? It aims to understand the social representations about the professionalism of the teacher for teachers of basic education in the Fluminense. Hence bringing outline the implications of these representations for their training. It is believed that the study of social representations allow focus on understanding ways of coping with the teaching career, thus contributing to the discussion of teacher training. To realize the desired, this research is anchored in the work of Moscovici (2003), Jodelet (2005), Gatti and Baker (2009); Gatti (2010), Silva (2003), Facci (2004); Martelli and Manchope (2004), among others. The methodology of this research approach is quantitative and qualitative dimensions outlined under Novikoff (2010) and uses it as art, literature, Test Free Word Association (Abric, 1999) and the Inventory Valuation and Combat (CAN0-Vindel; MIGUEL Tobal, 1992). The results point to the first legal advances and setbacks as the standardization of training courses; indicate a second representation centered on discipline problem, not cause violence and learning, which exempts the teacher to seek knowledge for the improvement of teaching, third shows professionalization and institutionalization without being the valuation of autonomy, therefore, shifts the valuation of professionalism to the context absolving themselves of the responsibility to take it. In summary, the representations are laden with emotional values and generators coping despite not resort to scientific knowledge.